2014
DOI: 10.1371/journal.pone.0091981
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Distribution in Soil and Rice in the Vicinity of the World's Largest and Longest-Operating Tungsten Mine in China

Abstract: The objective of this study is to investigate tungsten (W) contamination in soil and its enrichment in rice in the area of the world's largest and longest-operating W mines in China. Root zone soil and rice plants were sampled at 15 sites in the agricultural field adjacent to W mines and analyzed for Al, Fe, Mn, Sc, and W contents and W chemical forms in the soil samples and W contents in the rice root, stem, leaf, and grain samples. Results showed that W content in the soil ranged from 3.99 to 43.7 mg kg−1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Comparison of the soil R values (0.06-0.09) from this study with those for other metals (Cd, Zn, Ni and As), encompassing a wide range of soil types [54][55][56][57], shows that typically W resupply is relatively poorly sustained. This is further supported by the high (>90%) non-available residual fraction of W observed in acidic and neutral soils [10,18,58]. Johannesson et al, [59] concluded that W adsorption with mineral surface sites intensifies with increased H + and Fe concentrations in oxic, suboxic and anoxic groundwater systems.…”
Section: Measurement Of W In Soils Using Pz Pf and Sf Dgt'smentioning
confidence: 92%
See 4 more Smart Citations
“…Comparison of the soil R values (0.06-0.09) from this study with those for other metals (Cd, Zn, Ni and As), encompassing a wide range of soil types [54][55][56][57], shows that typically W resupply is relatively poorly sustained. This is further supported by the high (>90%) non-available residual fraction of W observed in acidic and neutral soils [10,18,58]. Johannesson et al, [59] concluded that W adsorption with mineral surface sites intensifies with increased H + and Fe concentrations in oxic, suboxic and anoxic groundwater systems.…”
Section: Measurement Of W In Soils Using Pz Pf and Sf Dgt'smentioning
confidence: 92%
“…X-ray tubes) [5][6][7], industrial catalysts [8] and ammunition [9]. The country with the most acute W pollution problems is China [10]. In 2010, 85% of the 61,000 t of W that were produced worldwide that year came from within Chinese borders [10], with the mineral extraction activities concentrated in the south-eastern provinces of Jiangxi and Guangdong.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations